Forensic Examination as the Main Form of Using Special Knowledge in the Civil and Arbitration Process - VORONIN, Sergey A. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).39, 2018)
Considering the classification of forensic examinations, it is necessary to consider the classification task of a General theory of judicial examination of common problems and practical forensic activities. This article reveals the full extent of the use of special knowledge from the expert during the examination in civil and arbitration process. Deals with the practical tasks of forensic activities, problems of the theory examination and the classification of expert tasks in the civil and arbitration process. It is interesting to consider another classification of expert tasks – the level of elaboration of methods of their solution. On this basis the tasks are divided into standard (algorithmization) and custom (heuristic, creative). Algorithmically the process of solving standard tasks are presented in the form of a developed and scientifically based techniques of expert research facilities – techniques of forensic examinations. It is interesting to consider another classification of expert tasks – the level of elaboration of methods of their solution. On this basis the tasks are divided into standard (algorithmization) and custom (heuristic, creative). Algorithmically the process of solving standard tasks are presented in the form of a developed and scientifically based techniques of expert research facilities – techniques of forensic examinations.